Profile of older people submitted to comprehensive geriatric assessment in a rehabilitation service - Rocha, Fernanda Silva (2017)
Objective: To describe the profile of older people submitted to comprehensive geriatric assessment in a rehabilitation service. Methods: Retrospective documentary descriptive study conducted at a rehabilitation service in Goiânia, Goiás, Brazil, with older patients submitted to Comprehensive Geriatric Assessment from December 2014 to December 2015. Information on gender, age, marital status, family arrangement, education, body mass index, polypharmacy, urinary incontinence, and physical activity were collected from medical records and submitted to statistical analysis. Results: The mean age of the population was 70.4 years (± 7.8). In all, 67.45% (n=228) of the participants are women, 50.29% (n=170) have 1-4 years of study, 44.38% (n=150) are married, 56.21% (n=190) live with relatives, and 77.51% (n=262) are sedentary. Urinary incontinence is prevalent in 49.53% (n=107) of the women, although it is quite relevant in men, with a rate of 21.81% (n=24). In all, 48.82% (n=165) of the participants presented polypharmacy, 77.51% (n=262) are sedentary and 59.17% (n=171) are overweight. Conclusion: Most participants are young old, women, sedentary, have low education, are married, live with relatives, and are overweight. The highest prevalence of urinary incontinence and polypharmacy occurs in women.